2021
DOI: 10.3390/vaccines9091020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Commercial Vaccines for the Protection of Piglets against the Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus (hp-PRRSV) QH-08 Strain

Abstract: Vaccination is the best way to prevent economic losses from highly pathogenic porcine reproductive and respiratory syndrome virus (hp-PRRSV) disease. However, the commercially available vaccines need to periodically evaluate their efficacy against infections caused by new hp-PRRSV variants. Therefore, the objective of this study was to evaluate the efficacy of four (two modified live vaccines (MLV) and two inactivated) PRRSV commercial vaccines in piglets challenged with QH-08 and to estimate the genetic dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 16 , 23 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China. All QYYZ-like strains were recombined with other lineages of PRRSV except the prototype strain QYYZ.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of this study and previous studies, QYYZ-like strains have been occasionally reported in northern China ( 19 , 26 , 28 , 53 ) but are mainly prevalent in southern and central China ( 12 16 , 23 25 , 27 , 29 , 30 , 32 ). Although recombination of PRRSV is very common, many non-recombination strains of JXA1-like ( 54 ), VR2332-like ( 28 ) and NADC30-like/NADC34-like PRRSV ( 7 , 55 ) have been reported after long-term evolution in China. All QYYZ-like strains were recombined with other lineages of PRRSV except the prototype strain QYYZ.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, given the prevalence of PRRS, vaccination remains the primary approach available. Commercially available vaccines in China include CH-1a/CH-1R, R98/R98 MLV, VR2332/Ingelvac PRRS MLV, JXA1/JXA1-R, TJ/TJM-F92, HuN4/ Hun4-F112, GD/GDr180, and among others ( Leng et al, 2017 ; Wang H. M. et al, 2018 ; Ding et al, 2021 ). While these vaccines can partially control PRRS outbreaks and reduce the duration of clinical signs and viremia in pigs, they cannot provide full protection against PRRS infection, with vaccine efficacy limited to partial or modest protection against heterologous challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is important to prevent and control PRRSV and to eliminate PRRSV ( Chen N. et al, 2021 ; Jeong et al., 2021 ). Although the PRRSV vaccine has a good protective effect against homologous strains, its protective effect against heterologous strains is incomplete ( Chen X. et al, 2021 ; Ding et al., 2021 ; Li Y. et al., 2021 ). In this study, immunization with an MLV vaccine provided some protection against NADC30-like PRRSV SX-YL1806 in piglets, including an improvement in temperature, ADG level, viremia, and lung tissue virus load ( Fig.…”
Section: Discussionmentioning
confidence: 99%